1993
DOI: 10.1002/j.1552-4604.1993.tb05616.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nifedipine on the Pharmacokinetics and Dynamics of Diltiazem: The Preliminary Study in Normal Volunteers

Abstract: To evaluate the influence of nifedipine on the pharmacokinetics and the pharmacodynamics of diltiazem, five healthy subjects received 60 mg diltiazem orally on two occasions, diltiazem alone or after nifedipine pretreatment (10 mg three times daily for 3 days). After nifedipine pretreatment, the maximum concentration (Cmax) of diltiazem was increased and the time of Cmax was shortened, and the area under the concentration curve (AUC) tended to be increased. Although heart rate was increased, the corrected PQ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Less well appreciated is the fact that nifedipine influences the pharmacokinetics of diltiazem. Early observations have found that pretreatment with nifedipine increased diltiazem concentrations, presumably secondary to both a decrease in its hepatic clearance as well as an increase in its bioavailability 23 . Thus, the interaction between verapamil and diltiazem and a DHP CCB can be exploited clinically to more effectively treat the hypertensive patient 24 …”
Section: Pharmacokinetic Drug‐drug and Nutritional Interactionsmentioning
confidence: 99%
“…Less well appreciated is the fact that nifedipine influences the pharmacokinetics of diltiazem. Early observations have found that pretreatment with nifedipine increased diltiazem concentrations, presumably secondary to both a decrease in its hepatic clearance as well as an increase in its bioavailability 23 . Thus, the interaction between verapamil and diltiazem and a DHP CCB can be exploited clinically to more effectively treat the hypertensive patient 24 …”
Section: Pharmacokinetic Drug‐drug and Nutritional Interactionsmentioning
confidence: 99%
“…Early laboratory investigations provide a theoretic basis for the additive nature of CCB response. These studies suggested a synergistic effect on receptor binding, 22 as well as increased drug concentrations, when diltiazem and a dihydropyridine CCB were concurrently used 23–26 …”
Section: Hypertensionmentioning
confidence: 99%
“…Less well appreciated is the fact that nifedipine influences the pharmacokinetics of diltiazem. Early observations showed that pretreatment with nifedipine increased diltiazem concentrations, presumably secondarily to both a decrease in its hepatic clearance and an increase in its bioavailability 23 …”
Section: Dual Calcium Channel Blocker Therapymentioning
confidence: 99%